A Qualitative Study of Indian Children's Perspectives on Peer Conflicts. (September 2013) - Dhillon, Megha; Babu, Nandita
This qualitative investigation explores children's perceptions of conflicts with peers in the school setting. Forty girls and boys from grades one and five (mean ages 6.4 years and 10.5 years respectively) were interviewed. Results were analysed using the interpretative phenomenological approach. Children reported having conflicts most often over instances of physical and verbal provocation. While younger children reported lower frequencies of peer conflict, older girls perceived such events to be a regular occurrence. Moreover, younger children reported conflicts to be short-lived while older children believed that the duration of conflicts depended on their intensity. Anger was frequently mentioned in relation to conflicts. Sadness was associated with conflicts with friends but not with non-friends. Older boys believed that controlling anger was essential for ending conflicts while girls felt that feelings of sadness and regret motivated them to resolve conflicts. Children reported settling disputes through various strategies like apologising and negotiation. Intense conflicts were perceived to entail negative consequences and were thus considered best avoided. Yet, factors like anger and impulsivity were believed to push children into fights. Implications of the findings have been discussed.